2018
DOI: 10.29252/jafm.11.04.28599
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Wedge Effect on the Seakeeping of a Planing Hull in Irregular Waves at the Onset of the Planing Region

Abstract: In the current paper, different experiments are conducted on a high speed planing craft in irregular waves, with and without a wedge. Performance and seakeeping aspects of these planing hulls in the form of trim, rise-up, and resistance in regular waves and heave, pitch, bow, and center of gravity (CG) acceleration in irregular waves are extracted in time series. Irregular waves represent sea state 3 with 12cm height and peak period of 1.66. A model length of 2.63m and 1:5 scale is considered and all data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Results of the nonstep model, which are extracted by Ghadimi et al [42], along with experimental measurements obtained in the present study are presented in Tables 5 and 6 at 1 to 8 m/s speeds. e diagrams of resistance, trim, and rise-up are also given versus Froude number in Figure 4 for better comparison.…”
Section: Deadrisementioning
confidence: 65%
See 1 more Smart Citation
“…Results of the nonstep model, which are extracted by Ghadimi et al [42], along with experimental measurements obtained in the present study are presented in Tables 5 and 6 at 1 to 8 m/s speeds. e diagrams of resistance, trim, and rise-up are also given versus Froude number in Figure 4 for better comparison.…”
Section: Deadrisementioning
confidence: 65%
“…Experiments are conducted on a nonstep and a single-step model with the same shape in the National Persian Gulf Towing Tank, and results are used to validate the numerical results. e nonstep model is previously tested by Ghadimi et al [42], while the single-step model is examined in the present study. e length and beam of the model are 2.64 m and 0.551 m, respectively, and the model has a constant deadrise angle of 24°.…”
Section: Experimental Testsmentioning
confidence: 99%
“…After that, the rooster tail of wedgemounted hulls was analyzed in a more comprehensive study via both experimental and numerical methods by Mahdi Sajedi et al [31]. Te seakeeping of wedgemounted hulls in irregular waves was also studied experimentally by Ghadimi et al [32]. In the case of stepped hulls, Sajedi et al [29] probed how a single-stepped hull with a step at 30% of vessel length to its stern performs in calm water and Froude numbers from 0.43 to 3.87.…”
Section: Introductionmentioning
confidence: 99%
“…Tey found that the simultaneous use of stern wedges and transverse steps could improve the vessel's undesirable performance prior to planing regime, which is one of the challenges in planing hull design. Tese extensive data [9,28,29,[31][32][33][34][35][36][37] for diferent confgurations of a single parent model present a unique opportunity to realize how diferent confgurations of step and wedge could afect a planing hull's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Other conducted research on the planing vessels is related to the performance of the vessel in calm water, experimentally, and numerically. 3543 Pennino et al. 44 investigated the dynamic trim and resistance of a warped model in calm water using experimental and numerical methods.…”
Section: Introductionmentioning
confidence: 99%